How does online social interaction promote students’ continuous learning intentions? - Zhang, Shunan; Che, ShaoPeng; Nan, Dongyan; Kim, Jang Hyun (Frontiers in Psychology, 2023)
Learning from online videos using synchronized Danmu comments provides a co-learning experience. To explore the factors influencing learning with or without Danmu videos, an initial set of reasons and impediments was compiled based on a pilot study of 12 Chinese university students who have the experience of learning with Danmu videos. Three hundred Chinese university students who have the experience of learning with Danmu videos were then surveyed to determine the factors that influence their motivations and hindrances. The potential predictors of users’ continuance intentions were also examined. The results showed that seeking information, social presence and perceived entertainment motivates learners and positively impacts their continuance intention to learn using Danmu videos. Hindrances include attention failure, visual obstacle, and information pollution but only attention failure and visual obstacle are negatively associated with learners’ continuance intention in the long run. Our findings provide constructive suggestions for addressing the issue of dropout rates, and novel ideas for future studies are proposed.